Transcriptomics in aquaculture: current status and applications - Sathyajith Chandhini; Vattiringal Jayadradhan Rejish Kumar (Reviews in Aquaculture, 2019)
Transcriptomics is the analysis of total RNA transcript in a cell, which gives a broad idea of cellular processes that are active and dormant. Recent advancement in next‐generation sequencing technologies like high‐throughput mRNA sequencing ( RNA ‐seq) facilitates in deciphering the functional complexity of the whole transcriptome of an organism. In the recent past, transcriptome profiling has been widely used in aquaculture for effective identification and expression analysis of candidate genes involved in growth, reproduction, development, immunity, disease, stress and toxicology. On the paucity of a comprehensive genome sequence, transcriptomics enables the detection of molecular markers such as simple sequence repeats and single‐nucleotide polymorphism associated with the trait of interest. This review summarizes the process of transcriptome analysis and the current state of transcriptomics in aquaculture related to diseases and immunity, reproduction and development, growth and nutrition, toxicology and stress. Further, this review highlights the application of transcriptomics, including generation of genetic resources, differential gene expression, analysis of molecular pathways and development of molecular markers.